The Vegetational Relations of Weathering, Frost Action, and Patterned Ground Processes, in the Mesters Vig District, Northeast Greenland. - Raup, Hugh M. (Meddelelser om Grønland, 1971)
Botanical descriptions and analyses presented in this paper apply to representative sites selected from those discussed by WASHBURN in "Weathering, frost action, and patterned ground in the Mesters Vig district, Northeast Greenland" (Meddr Grønland 1969, Bd. 176 No. 4). They deal with vegetation-site relations in the following habitat complexes: rocky hilltops, ledges, crevices and talus; simple and compound nonsorted circles and their included small nonsorted polygons; small sorted and nonsorted polygons on emerged delta remnants; large nonsorted polygons; debris islands; and large sorted nets. Site factors used are: coverage of the ground by vascular plants; moisture supply; and physical disturbance of the soil by frost - and nonfrost-induced geomorphic processes. The vegetations are analyzed with respect to their species’ tolerance of variation and intensity in the factor gradients. A summary compares the sites in terms of the relative proportions of wide, intermediate and narrow tolerance shown by their vascular floras on each of the gradients. The analyses presented show, as did those made for the mass-wasting sites, positive correlations between the local distribution of species tolerance and the local behavior of the site factors of coverage, moisture and physical disturbance. They suggest further that the ratings of species tolerance made from general observations are sufficiently valid to be useful as indicators of these site conditions.